The Influence of Brand Reputation and Electronic Word of Mouth with Brand Trust as a Moderating Variable on Purchasing Decisions within the TikTok Shop Application - Andri Astuti Itasari; Buddy Riyanto; Saiful Bahri (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This study aims to determine the effect of brand reputation and electronic word of mouth (e-WOM) with brand trust as a moderation on purchasing decisions on the TikTok Shop application. This study focuses on seeing the re-emergence of the TikTok Shop application for consumers. Employing a quantitative descriptive methodology, this study is categorized as explanatory, aiming to clarify whether there is an influence between those two phenomena. The methodology research is a survey. The population of this study was active male and female students of Slamet Riyadi University, Faculty of Social and Political Sciences, Class of 2023, while the sample was 100 male and female students of Slamet Riyadi University, Surakarta, who purchased products on the TikTok Shop application. Data collection encompasses both primary and secondary data sources. Multiple linear regression analysis is employed for data analysis, complementing the absolute difference test for robustness. The results of the study show that partially brand reputation has a significant effect of 0.015, electronic word of mouth and brand trust of 0.000, while brand reputation on purchasing decisions moderated by brand trust is 0.446 and electronic word of mouth on purchasing decisions moderated by brand trust is 0.559. So, brand reputation, e-WOM and brand trust have significant influence to purchasing decision, while brand reputation and e-WOM on purchasing decision by brand trust in TikTok Shop application are not proven because Ho is accepted.